Restorative Justice Process in Juvenile Delinquency in Samut Sakhon Juvenile and Family Court - Wongprasertkarn , Wilai; Kangsadanporn, Korn (Journal of Dhamma for Life, 2025)
This study aims to examine restorative justice processes in criminal proceedings for children and youth at the Samut Sakhon Juvenile and Family Court, as well as to investigate the roles and challenges of practitioners in the rehabilitation and treatment of children, youth, and their families. A qualitative research approach was employed, collecting data through in-depth interviews and focus group discussions with key informants, including the Chief Judge and Juvenile and Family Court Judges 2, court psychologists 2, the Court Director 1, and Associate Judges 5. The findings indicate that restorative justice processes emphasize relationship restoration and problem-solving rather than punishment. Key practices include mediation, compensation for damages, and rehabilitation, which help reduce recidivism, promote accountability, and foster mutual understanding among offenders, victims, and the community. Psychologists play a critical role in assessment, counseling, and coordinating rehabilitation, while counselors and meeting coordinators support and facilitate group sessions. Major challenges include limited psychological knowledge and counseling skills among some practitioners, role confusion, and familial conflicts that hinder rehabilitation efforts. Recommendations to enhance restorative justice include providing training on psychology and counseling techniques, conducting workshops on coordinating restorative meetings for associate judges, and organizing regular seminars to share experiences and address operational challenges. These measures aim to strengthen the effectiveness and sustainability of restorative justice practices for children and youth in Samut Sakhon.